Environmental incomes sustained as provisioning ecosystem service availability declines along a woodland resource gradient in Zimbabwe. (October 2019) - Pritchard, Rose; Grundy, Isla M.; van der Horst, Dan; Ryan, Casey M.
Highlights: We quantify provisioning services and household incomes in rural Zimbabwean. Low woodland cover reduces availability of key provisioning services. No relationship between provisioning service availability and environmental income. Most resources can be derived from more disturbed woodlands or non-wooded land. Promising new approach for exploring resource use in forest-agriculture mosaics. Abstract: Forest and woodland resources can play a key role in rural livelihoods in the Global South, making it critical to understand what forest change could mean for rural wellbeing. Calculating environmental income has become a popular method of highlighting the importance of environmental resources in livelihoods, but few studies have quantified both provisioning ecosystem service availability and environmental income in the same landscape, or disaggregated environmental income by source land cover. This limits our ability to anticipate how forest change could impact rural livelihoods and could result in management interventions detrimental to vulnerable groups. The objective of this study was therefore to explore links between woodland cover, provisioning ecosystem service availability and household environmental income by applying a novel interdisciplinary approach in six villages on a gradient of woodland resource availability in Zimbabwe. We firstly use techniques from quantitative ethnobotany to score the species underpinning six locally important provisioning ecosystem services, and combine these scores with data from 80 tree survey plots to establish provisioning service availability. We then use income data from 91 households to explore relationships between provisioning service availability and household income portfolios. We find that villages with less woodland have lower availability of all studied ecosystem services and also a lower diversity of species underpinning service provision, but that there are no significant relationships between woodland resource availability and environmental income, livelihood diversity or intra-community income inequality in the case study area. We suggest that income portfolios are very resilient to woodland loss because households can still derive significant resources from woodlands which would be considered degraded in ecological terms and can draw upon kin networks which facilitate access to resources beyond village boundaries. The novel combination of approaches used in this study, particularly if applied at greater spatial and temporal scales, can provide valuable insight into the complexities of resource use in forest-agriculture mosaics.